Bishop, Special Crimes : Curse of Salem - Book 20 - Hooper, Kay (Thorndike, Maine : Center Point Large Print, 2022)
"The small town of Salem has been quiet for months -- or so Bishop and his elite Special Crimes Unit believe. But then Hollis Templeton and Diana Hayes receive a warning in Dianas eerie "gray time" between the world of the living and the realm of the dead that a twisted killer is stalking Salem, bent on destroying -- in the most bloody and horrifying way possible -- the five families that founded the town. The stakes are high, especially for new friends Nellie Cavendish and Finn Deverell, both members of the Five, and this time Bishop and his wife Miranda will lead the team to hunt down a vicious killer and uncover a horrifying secret haunting Salem"--
Keywords: Bishop, Noah -- (Fictitious character) -- Fiction; United States -- Federal Bureau of Investigation -- Fiction; Government investigators -- Fiction; Serial murder investigation -- Fiction; Blessing and cursing -- Fiction; North Carolina -- Fiction; Suspense fiction; Paranormal fiction; Thrillers (Fiction)